Traces of Blessing and Birthright: Revealing the Narrative of Jacob and Esau in a Fresh Perspective - Sibagariang, Julius Stefanus (Sekolah Tinggi Teologi Baptis Indonesia, 2025)
This study aims to rediscover the classic narrative of Jacob and Esau in the Book of Genesis, focusing on the concepts of blessing and birthright and their theological and cultural significance. It examines these concepts fresh, considering their deeper spiritual, social, and historical dimensions. Through a critical historical hermeneutic approach and comprehensive textual analysis, this research examines how the relationship between Jacob and Esau reflects personal tensions and reveals the broader dynamics of blessing and birthright within the cultural context of ancient Israel. Ultimately, this study offers a new perspective on the long-standing narrative, providing richer insights into the theological and social implications of the story of Jacob and Esau, particularly concerning the themes of blessing and birthright.